Approaches For Transdermal Drug Delivery System:A Review - Snehal, Thakre; Shinde, Madhuri (Asian Journal of Pharmaceutical Research and Development, 2014)
As the oral route of drug delivery system shows number of side effects such as gastric irritation, fluctuation in drug level in plasma, hepatic first pass metabolism.The Transdermal drug delivery system (TDDS) provides the effective way to deliver the drug directly in systemic circulation and hence increase in therapeutic effect of the drug. Topical administration of therapeutic agents offers many advantages over conventional oral and other routes of drug delivery.Transdermal administration of drugs is an another way of administration that can significantly deliver the larger molecules in potent quantities that overcome the problem with the oral administration such as poor bioavailability due to first pass metabolism and gastric irritation.To improve the effectiveness of the transdermal drug delivery system, number of approaches are emerged,which will increase the absorption of the drug in systemic circulaton and reduction in dosing frequency.This review article describes the number of approaches for transdermal drug delivery system.